Runoff Estimation and Water Demand Analysis for Holetta River, Awash Subbasin, Ethiopia Using SWAT and CropWat Models - Tibebe, M.; Melesse, A.M.; Zemadim, Birhanu (Springer, 2016)
This chapter discusses the hydrology of Holetta River , Ethiopia , its seasonal variability and water management in the watershed. Soil and Water Assessment Tool (SWAT) modeled the rainfall–runoff process of the watershed. Statistical [coefficient of determination (R 2), Nash–Sutcliffe efficiency coefficient (NSE), and index of volumetric fit (IVF)] and graphical methods were used to evaluate the performance of the model. The result showed that R 2, NSE and IVF were 0.85, 0.84 and 102.8, respectively, for monthly calibration and 0.73, 0.67 and 108.9, respectively, for monthly validation. These indicated that SWAT model performed well for simulation of the hydrology of the watershed. After modeling the rainfall runoff relation, the water demand of the area was assessed. CropWat model was applied and survey analyses were performed to calculate the water demand in the area. The total water demand for the three major users was 0.313, 0.583, 1.004, 0.873, and 0.341 million cubic meters (MCM) from January to May, respectively. The average flow obtained from SWAT simulation was 0.749, 0.419, 0.829, 0.623, and 0.471 MCM from January to May, respectively. From 5 months, the demand and the supply showed a gap during February, March, and April with 0.59 MCM. To solve the gap created by the demand, alternative source of water supply should be studied and integrated water management systems should be implemented.